2006
DOI: 10.1002/jssc.200600206
|View full text |Cite
|
Sign up to set email alerts
|

Determination of some hydroxybenzoic acids and catechins in white wine samples by liquid chromatography with luminescence detection

Abstract: A liquid chromatographic method with luminescence detection for the determination of eight phenolic compounds is reported. The method involves postcolumn derivatization with terbium(III). This derivatization is based on the reaction between phenolics and terbium(III) to form luminescent chelates, which were determined at lamda ex 295 and lamda em 545 nm using the fluorescence mode. The long wavelength emission of lanthanide chelates can minimize interferences from background sample matrix, which usually emit a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
(39 reference statements)
1
17
0
Order By: Relevance
“…Phenolic acids, comprising mainly of caftaric, coutaric, fertaric, and tartaric, are normally found as esters. Hydroxycinnamic esters are one of the most abundant groups of phenolic compounds found in grapes (Rodríguez et al, 2006). Stilbene-like compounds include resveratrol, its glucoside piceid, astringin and viniferins.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic acids, comprising mainly of caftaric, coutaric, fertaric, and tartaric, are normally found as esters. Hydroxycinnamic esters are one of the most abundant groups of phenolic compounds found in grapes (Rodríguez et al, 2006). Stilbene-like compounds include resveratrol, its glucoside piceid, astringin and viniferins.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical comparison of the results with the HPLC method showed a good agreement and indicates no significant difference in accuracy and precision. So, the detection limit of 0.11 µg mL -1 can be achieved, much better than those provided by fluorimetric [11] or even by HPLC [5] methods. Also, the precision of the proposed method of analysis was found to be good (RSD < 5 %).…”
Section: Resultsmentioning
confidence: 87%
“…The analysis of free phenolic acids in wines has been extensively studied by liquid chromatographic methods [4][5][6][7][8][9][10][11][12][13][14][15][16]. Diode array detection has been extensively used for the development of liquid chromatography methods [5,8,9,10,12,14,15], whereas fluorimetric [6,11] and mass spectrometry [4,16] detection system has been used to a lesser extent. Most fluorimetric methods proposed have lower detection limits than photometric methods, but these methods have not been widely used in practice because the species that can be detected are limited [6,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-7 recovery of OTA from 1 ppb (ng/mL) OTA standard solution by Automated pMISPE-PE-HPLC-FD analysis of red wineRed wines are composed o f a complex mixture o f water, phenolic compounds, organic acids, alcohols, and residual sugars[118]. Some study revealed that the chemical composition o f wine is containing more than 500 different compounds in a wide and MIPPy/CNTs/QDs-modified needles of different total surface areas range o f concentrations[119]. Because o f many interfering compounds that exist in red wine, one general problem in the HPLC-FD determination o f OTA in red wine samples would be the interference from florescent matrix components (polyphenols).…”
mentioning
confidence: 99%